Iniciativa Social: DesPrenda - Lora Valdivieso, María Alejandra (2020)
DesPrenda is a social initiative that arises after the mandatory social distancing caused by the COVID-19. The aim of the organization is to bring personalized clothing kits to dress 37 families of the NSE D and E who live in Los Pinos, Vista Alegre, Santa Cruz and Praderas Baja de Pamplona Alta in San Juan de Miraflores. Under the pillars of responsibility, sustainability, empathy and solidarity, a communication strategy was implemented between May and June through the Facebook and Instagram pages. More than 260 bags of clothes were collected through the modality of massive home collections, having a total of 66 donors. After the selection and classification of these bags, a total of 2016 clean and undamaged garments were distributed to 46 families, exceeding the initial objective and benefiting a total of 244 people.